Fingerprinting changes in source contribution for evaluating soil response during an exceptional rainfall in Spanish pre-pyrenees. (15th June 2019) - Gaspar, Leticia; Lizaga, Ivan; Blake, William H.; Latorre, Borja; Quijano, Laura; Navas, Ana
Abstract: In the Mediterranean region, floods are expected to increase as a result of climate change and knowledge of soil erosion hot spots during exceptional rainfalls is required to support mitigation measures. This study quantifies the main sediment sources during an exceptional rainfall event in 2012 (235 mm) at the outlet of two catchments located in NE Spain. To this purpose, suspended sediments were collected during the flood event, complemented with entrapped sediments in mat taken one year after the event. We used fingerprinting methodology and applied the FingerPro unmixing model to estimate the contribution from main sources. The selected tracers clearly distinguished agricultural, rangeland, subsoil and channel banks as the four potential sources in both catchments. In the Vandunchil catchment, the 8 time-integrated suspended sediment samples revealed changes in source contribution during the 2-h sampling sequence. There were relatively high contributions from rangeland, agriculture and subsoil at the beginning of the sampling, representing 30, 40 and 35% of the total source contributions, respectively. Our records captured the delivery of pulses of eroded surface soil transported by runoff with direct connectivity to the stream. The sequence was followed by a sharp increase in channel bank contribution (up to 90%) in comparison to the other sources, reflecting streambank erosion and landslide occurrence, which manifested during the flood. In contrast, in the La Reina catchment, agricultural soils contributed the most (65%) and, together with subsoils (32%), were the main sources. These results reflect the effect of the higher connectivity and slope gradient of these cultivated fields of the La Reina catchment in comparison with those of the Vandunchil catchment. We discuss the possibility of using different properties, such as radionuclides, geochemistry and magnetic measurements, as tracers to distinguish between potential sources during an exceptional event in upland Mediterranean catchments. Our results support the use of fingerprinting techniques to determine variations in source contribution and sediment provenance during flood events, as extreme rainfalls are main drivers of sediment mobilization and key factors in changing landscapes. This is essential in identifying vulnerable hot spots, in which early-stage interventions are needed, and for helping policy makers with management of soil and water resources. Graphical abstract: Image 1074 Highlights: Unique opportunity to capture soil response during an exceptional event of 235 mm. Suspended sediment properties changed during the flood event. Source contributions varied in response to the rainstorm in a short period. Switch from soil sources to channel bank provenance was captured during the flood. Land use and connectivity determined the suspended sediment provenance.